(untitled)
This article aims to study the development of Arabic poetry from its early phase to its modern one. Having used a historical-diachronic study of form and content of Arabic poetry, this article concludes that Arabic poetry, as the oldest genre in the Arabic literary tradition, has hardly developed. Not until the 20th century, more commonly known in the history of Arabic literature as As